Problems arising in connection with the protection of citizens' rights in administrative offenses ("Journal "U". Economy. Management. Finance.", 2025)
Within the framework of this study the author has considered the definition of administrative offenses. Special attention is paid to the analysis of current problems of law enforcement practice. Proposals to improve the mechanisms of protection of citizens' rights are presented. The importance of improving the legal culture of citizens is highlighted. The practical significance of the work lies in the fact that the results obtained in the course of the study can be applied in order to solve the existing problems.
Keywords: administrative offenses; problems; control; violation; law